Additional file 3 of Genomic evidence for sulfur intermediates as new biogeochemical hubs in a model aquatic microbial ecosystem - Adrien Vigneron (10162165); Perrine Cruaud (10162168); Alexander I. Culley (10162171); Raoul-Marie Couture (10162174); Connie Lovejoy (10162177); Warwick F. Vincent (10162180) (2021)
Additional file 2: Supplementary Figure S2. Relative proportion of bacterial lineages obtained with the different molecular approaches a) Relative proportion of bacterial lineages observed in the rRNA gene amplicon dataset and rRNA amplicon dataset. b) Relative proportion of bacterial lineages observed in the rRNA gene amplicon dataset and in the metagenomic dataset. Each point represents a bacterial lineage as defined in Supplementary Figure S1. Points are color coded according to their sample of origin.